Botulinum Neurotoxin-A Injection in Adult Cervical Dystonia and Spastic Paresis: Results From the INPUT (INjection Practice, Usage and Training) Survey - Chung, Tae Mo; Jacinto, Luis Jorge; Colosimo, Carlo; Bhatia, Kailash P.; Tiley, Julie; Bhidayasiri, Roongroj (Frontiers in Neurology, 2020)
Botulinum toxin-A (BoNT-A) is an effective treatment for cervical dystonia (CD) and spastic paresis (SP), but it requires in-depth knowledge of anatomy and injection techniques. The Ixcellence Network® is an educational programme to provide neurology, neuropaediatrics, and physical medicine and rehabilitation (PMR) specialists with access to best clinical practices and innovations regarding SP and CD management with BoNT-A. To assess the benefits of such educational programmes and identify unmet needs, a multidisciplinary scientific committee designed INPUT (INjection Practice, Usage & Training), an international multicentric survey describing training and practices among this trained and experienced population. A self-completed questionnaire was sent online to 553 trainees and 14 trainers from the Ixcellence Network®. Among the 131 respondents, 92% specialized in PMR (48%) or neurology (44%), with a mean experience of 15.5 years in their clinical fields and 10.9 years of BoNT-A injection. Most of them (98%) reported having received training before performing their first BoNT-A injection and attending specific courses on how to perform it without any instrumental guidance (76%), and with ultrasound (73%), electrical stimulation (44%) or electromyography (41%). In terms of practices, 92% of respondents reported using at least one guidance technique while injecting, with ultrasound being the most used technique (48%). Attending specific courses was significantly associated with greater self-confidence and use, e.g. for injection with ultrasound, mean self-confidence, on a scale from 1 (not confident) to 10 (fully confident), was 7.9 for trained respondents (vs 4.0 for untrained respondents, p < 0.001) of whom 70% stated that they used this technique regularly or systematically (vs. 11% of untrained healthcare professionals (HCPs), p < 0.0001). Moreover, 84% of respondents reported having trained colleagues, residents or fellows through theoretical (70%) or practical teaching in individuals (80%) or in small groups (65%). Overall, 86% of respondents reported a notable increase over the past 5 years of the number of patients treated with BoNT-A. INPUT is the first international survey describing training and practices in SP and CD management of physicians who attended a dedicated educational programme. The results highlighted the importance of training for self-confidence, and the use of specific techniques and new approaches.